PRESENT AND FUTURE OF COACH DEVELOPMENT RESEARCH AND PRACTICE: A CONVERSATION WITH PROFESSOR PIERRE TRUDEL - Milistetd, Michel (2021)
The field of sport coach development has changed considerably in the last decades and everything indicates that, in an increasingly volatile, uncertain, complex, and ambiguous world (VUCA world), many other changes will take place. It seems increasingly likely that ways will have to be found to harmonize on-the-job learning with the formal coach education programs from which qualifications are derived. In an attempt to analyze the present and to address some directions for the future of sport coach development research and practice, this insight paper presents the summary of a series of conversations with one of the researchers who has greatly influenced the development of sport coaches over the past 30 years, Professor Pierre Trudel.